Audio-guided mindfulness training in schools and its effect on academic attainment: Contributing to theory and practice. (December 2018) - Bakosh, Laura S.; Tobias Mortlock, Jutta M.; Querstret, Dawn; Morison, Linda
Abstract: We report the results of a randomized trial (N = 337) examining the effectiveness of a daily audio-guided MBI in raising academic achievement in 16 volunteer classrooms across two socio-demographically diverse United States primary schools. The study's findings were that, over the intervention period, improvements in Math scores, Social Studies scores and Grade Point Averages (GPA) were generally higher for students in intervention classrooms. However, confidence intervals were wide and there was pre-existing variability between schools and grades, resulting in few significant differences as a result of the intervention and generally low effect sizes. Through a careful discussion of the study's results, the paper contributes to theory by generating a comprehensive agenda for follow-up research. The study also contributes to practice by reporting on the effectiveness of technology-enabled mindfulness training because participating teachers seemed able to implement the intervention with almost no further training or need for hiring external mindfulness experts. Highlights: In an RCT the hypothesized link between mindfulness training and attainment was examined. Pre-recorded audio-guided mindfulness training was used as the daily school intervention. Some promising results were found for Social Studies, GPA, and especially Math scores. The lack of consistent statistically significant benefits resulted in a detailed research agenda for follow-up work. It seems feasible to embed technology-based mindfulness in schools without extensive teacher training or external experts.